Tinjauan Denominasi Mayor Dalam Konsep Ketuhanan Hindu - Ida Bagus Wika Krishna (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Discussion of God, that the terminology is called Theology, being debated, particularly in the Hindu. Some claimed that Hinduism cannot be equated with the theology, because the term is associated with the Western Catholic Christiahity. However, if the Godhead as a concern, each denomination within Hinduism has its own concept, including the proceduresfor conducting rituals, codes of ethics, prayer rooms and others. These concepts may be lent theological terms. In this article is discussed about the divinity of several Hindu denominations briefly. Among the many denominations, this work just to show the tradition of Saiva, Vaishnava, Sakta, Smarta, and Tantra, because, these tradition are still practiced and each of them has a great follower. Each denomination has its uniqueness in view God as well as a process to reach Him.